Sustaining Competitive Advantages in Malaysian Electrical and Electronics Industries Context - BakAun Teoh; NoorHidayah Abu (International Journal of Supply Chain Management, 2018)
Electrical and electronics (EE) manufacturing industries is one of the main sources for overall Malaysia economic growth. Generally, development and innovation of new product in EE companies involved the changes in the finished goods, products or services offered by the company. However, Malaysia EE industries are lagging behind in terms of technological research and development and corporate strategy in adopting organizations flexibility in facing fierce market competition. In this technology advancement era, most multinational electrical and electronics (EE) conglomerate has introduced research and development (RD) in product technology to be integrated in manufacturing system in order to sustain competitive advantages.